Variety: models of multiple-discreteness - Kim, Jaehwan (Henry Stewart Talks, 2010)
Issue of multi-item buying behavior in scanner-panel data, Preference and satiation in consumer behavior, Economic theory for multiple-discreteness and challenges in model building, How to build models at product offering level, How to build models at product characteristic level, Application of models to marketing decision, Discussion on future direction for model extension